Produção de geleia real em colônias com rainhas selecionadas, diferentes manejos e fornecimento de ração - Pereira, Heber Luiz (2013)
This research was carried out to evaluated the royal jelly production in two genetic groups of Africanized honey bees (Apis mellifera L.), selected for royal jelly or honey production, submitted to two systems of positions of queen excluder in the nucs, with and without ration supply. 20 colonies selected in overlapped nucs were distributed in completely randomized design. Graftings were put inside the third nuc. It was made 24,180 graftings, and 403 royal jelly collections. The production parameters were: percentage of the larvae accepted in the upper and lower bars, weight of thrown away larvae (mg), royal jelly per cup (mg), and royal jelly per colony (g). Data were analyzed using software Statistical Analysis System. The two genetic groups did not presented a different royal jelly production, but were influenced by the position of queen excluder, and the selected colonies for royal jelly and for honey increased their production in 50.2% and 36.9%, respectively, when handled with the queen confined inside the first nuc. The addition of ration did not improvement in this work.